Load estimation with uncertainties from opportunistic sampling data – A semiparametric approach - Wang, You-Gan; Kuhnert, Petra; Henderson, Brent (Journal of hydrology (Amsterdam), 2011)
► Established indices to quantify biases in flow and concentration data. ► Developed procedures to obtain representative flow data at regular time intervals for unbiased estimation of load. ► Constructed hydrologically meaningful variables such as discounted average flow to capture the exhausting process. ► Developed flexible semiparametric models for concentration prediction hence load estimation. ► Derived standard errors for the resulting load estimates. We consider estimating the total load from frequent flow data but less frequent concentration data. There are numerous load estimation methods available, some of which are captured in various online tools. However, most estimators are subject to large biases statistically, and their associated uncertainties are often not reported. This makes interpretation difficult and the estimation of trends or determination of optimal sampling regimes impossible to assess. In this paper, we first propose two indices for measuring the extent of sampling bias, and then provide steps for obtaining reliable load estimates that minimizes the biases and makes use of informative predictive variables. The key step to this approach is in the development of an appropriate predictive model for concentration. This is achieved using a generalized rating-curve approach with additional predictors that capture unique features in the flow data, such as the concept of the first flush, the location of the event on the hydrograph (e.g. rise or fall) and the discounted flow. The latter may be thought of as a measure of constituent exhaustion occurring during flood events. Forming this additional information can significantly improve the predictability of concentration, and ultimately the precision with which the pollutant load is estimated. We also provide a measure of the standard error of the load estimate which incorporates model, spatial and/or temporal errors. This method also has the capacity to incorporate measurement error incurred through the sampling of flow. We illustrate this approach for two rivers delivering to the Great Barrier Reef, Queensland, Australia. One is a data set from the Burdekin River, and consists of the total suspended sediment (TSS) and nitrogen oxide (NO x ) and gauged flow for 1997. The other dataset is from the Tully River, for the period of July 2000 to June 2008. For NO x Burdekin, the new estimates are very similar to the ratio estimates even when there is no relationship between the concentration and the flow. However, for the Tully dataset, by incorporating the additional predictive variables namely the discounted flow and flow phases (rising or recessing), we substantially improved the model fit, and thus the certainty with which the load is estimated.